Analisis Potensi Pembangkit Listrik Tenaga GAS Batubara di Kabupaten Sintang - Sulistyono, Dedy (Faculty of Engineering, Universitas Tanjungpura, 2012)
Abstract The calculation of coal analysis it can be concluded that, in order to produce coal consumption in one day at least, the cost of fuel per day of most small, average fuel costs - the rate per Kwh small, and the average consumption of fuel per Kwh the smallest, using bituminous coals calorie 6570, and located in the middle of the Village District Ketungau Semelitang. Keywords Batubara,Gas, Bahan Bakar.